2007
DOI: 10.1074/jbc.m603606200
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Pathophysiological Role of Endogenous Methylarginines in Regulation of Endothelial NO Production and Vascular Function

Abstract: In endothelium, NO is derived from endothelial NO synthase (eNOS)-mediated L-arginine oxidation. Endogenous guanidinomethylated arginines (MAs), including asymmetric dimethylarginine (ADMA) and N G -methyl-L-arginine (L-NMMA), are released in cells upon protein degradation and are competitive inhibitors of eNOS. However, it is unknown whether intracellular MA concentrations reach levels sufficient to regulate endothelial NO production. Therefore, the dose-dependent effects of ADMA and L-NMMA on eNOS function w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
175
2
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 223 publications
(187 citation statements)
references
References 55 publications
9
175
2
1
Order By: Relevance
“…In the presence of physiologically relevant L-Arg levels (100 M), ADMA treatment resulted in a dose-dependent inhibition of endothelial NO with Ͻ20% inhibition seen at ADMA concentrations of 5 M. Overall, these results demonstrate that L-Arg supplementation can only partially restore the loss in NO production occurring after ADMA administration. Although the addition of exogenous L-Arg would be expected to fully restore ADMA-mediated eNOS inhibition, these results are consistent with previous studies demonstrating partial restoration of endothelial NO with L-Arg following exposure to exogenous ADMA (18) (Fig. 9).…”
Section: Effects Of Ddah-1 and -2 Overexpression On Endothelial Nosupporting
confidence: 81%
See 3 more Smart Citations
“…In the presence of physiologically relevant L-Arg levels (100 M), ADMA treatment resulted in a dose-dependent inhibition of endothelial NO with Ͻ20% inhibition seen at ADMA concentrations of 5 M. Overall, these results demonstrate that L-Arg supplementation can only partially restore the loss in NO production occurring after ADMA administration. Although the addition of exogenous L-Arg would be expected to fully restore ADMA-mediated eNOS inhibition, these results are consistent with previous studies demonstrating partial restoration of endothelial NO with L-Arg following exposure to exogenous ADMA (18) (Fig. 9).…”
Section: Effects Of Ddah-1 and -2 Overexpression On Endothelial Nosupporting
confidence: 81%
“…In support of this hypothesis, we and others have demonstrated that endothelial ADMA levels increase 3-4-fold in restenotic lesions and in the ischemia reperfused myocardium (18,40). Based on the kinetics of cellular inhibition, these concentrations of ADMA would be expected to elicit a 30 -40% inhibition in NOS activity (18). These studies, however, involve lesionspecific increases in ADMA and are not associated with increased plasma levels of ADMA and would not be expected to contribute to systemic cardiovascular pathology.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…ADMA is the most abundant endogenous inhibitor of NO system, 33 and it dose-dependently inhibits NO synthase at concentration in the range of values actually attained in patients with CKD. 34 FGF-23 and the associated co-receptor Klotho impinge on the same system. Indeed, Klotho knockout mice 35,36 (i.e., animal models characterized by high plasma levels of FGF-23 37 ) do not express NO synthase in the vascular system and exhibit almost abolished response to acetylcholine, the strongest stimulant of NO activity.…”
Section: Discussionmentioning
confidence: 99%